Hurford’s Constraint and Disjunctions over Speech Acts - Krifka, Manfred (Proceedings of the Amsterdam Colloquium, 2024)
The paper focuses on apparent exceptions to Hurford’s generalization on disjunctions of the type John was born in Paris or at least in France and John was born in France or even in Paris. It argues that such cases are disjunctions of speech acts of different strength. For this reason, the assertion with the stronger proposition does not license the other one, nor vice versa, hence Hurford’s generalization is not violated. The paper raises the issues of disjunctions of speech acts and of assertive strength, and also reconsiders apparent exceptions of the type Some or all of the children are sick.